Adaptive Processes in Hearing. (March 2018) - Santurette, Sébastien; Christensen-Dalsgaard, Jakob; Tranebjærg, Lisbeth; Andersen, Ture; Poulsen, Torben; Dau, Torsten
Our auditory environment is constantly changing and evolving over time, requiring us to rapidly adapt to a complex dynamic sensory input. This adaptive ability of our auditory system can be observed at different levels, from individual cell responses to complex neural mechanisms and behavior, and is essential to achieve successful speech communication, correct orientation in our full environment, and eventually survival. These adaptive processes may differ in individuals with hearing loss, whose auditory system may cope via "readapting" itself over a longer time scale to the changes in sensory input induced by hearing impairment and the compensation provided by hearing devices. These devices themselves are now able to adapt to the listener's individual environment, attentional state, and behavior. These topics related to auditory adaptation, in the broad sense of the term, were central to the 6th International Symposium on Auditory and Audiological Research held in Nyborg, Denmark, in August 2017. The symposium addressed adaptive processes in hearing from different angles, together with a wide variety of other auditory and audiological topics. The papers in this special issue result from some of the contributions presented at the symposium.